Minimalist Sofa Redesign Using the Kano Method: Perancangan Ulang Sofa Minimalis Menggunakan Metode Kano - Yusuffa, Depry; Jakaria, Ribangun Bamban (Procedia of Engineering and Life Science, 2023)
UKM Mebel Berkah Raya is a company engaged in the field of furniture, one of the products produced is Sofa products. The large number of competitors who are the company's competitors, makes it difficult for the products produced to compete with similar products on the market, therefore, the company conducts a preliminary survey involving loyal customers owned by UKM Mebel Berkah Raya, in order to find out the desires of customers for sofa products, especially sofa products that are produced by the UKM furniture, Berkah Raya. The data obtained shows that the problem that is owned by the product sofa produced by UKM Mebel Berkah Raya lies in the product design attributes, so that with the problems that are owned, further research is carried out which aims to find out in detail the problems that are owned, to then carry out re-design of the sofa product, so that it will produce a sofa product that is in accordance with the customer's wishes. This study uses the Kano method to determine the level of customer satisfaction with a product by paying attention to the attributes attached to the product. so that the level of urgency of each Voice of Customers, so that action can be taken according to the priority level of the results obtained. The results of this study are that the attributes that will be developed with the provisions of Attractive that produce customer satisfaction. attributes Indiffrent that can generate positive feedback with customers.attribute One-Dimantion can increase customer satisfaction. So that the resulting design in the form of an existing sofa design is representative of the measurements that have been carried out with the method used.